Knowledge of the ovulatory cycle and its determinants among adolescent females in Ghana - Grace Frempong Afrifa-Anane (BMC Women's Health)
Abstract Background Good knowledge about the ovulatory cycle plays an important role in reducing unwanted pregnancies and unsafe abortions among adolescent females. However, in Ghana, knowledge of the ovulatory cycle among adolescent females is not well studied. Thus, this study sought to assess adolescent females’ knowledge regarding the ovulatory cycle and its determinants in Ghana. Methods This study used data from the 2022 Ghana Demographic and Health Survey. It comprised a sample of 2,835 adolescent females (Mean age = 16.9, standard deviation ± 1.42). Multilevel multivariable logistic regression was used to analyse the determinants of ovulatory cycle knowledge among Ghanaian adolescent females. Four models were fitted incorporating individual and community levels. All associations were considered statistically significant at 95% confidence level in the fixed effect results. The random effects were quantified in terms of Intra-Class Correlation (ICC) and Primary Sampling Units (PSUs) variance. Results The level of knowledge about the ovulatory cycle was 24.6% (95% CI=23.0-26.0%). Adolescent females with secondary/higher education (AOR = 2.36; 95% CI = 1.26–4.43), at least one child (AOR = 2.01; 95% CI = 1.40–2.89), used traditional contraceptives such as rhythm, withdrawal methods (AOR = 2.26; 95% CI = 1.52–3.67), menstruated in the last six weeks (AOR = 2.01; 95% CI = 1.08–3.57) and media exposure to family planning messages (AOR = 1.89; 95% CI = 1.52–2.35) had higher odds of having good knowledge about the ovulation cycle. At the community level, respondents who resided in communities with high literacy levels had higher odds of having good knowledge of the ovulatory cycle (AOR = 1.62; 95% CI = 1.14–2.31). Conclusions Knowledge of the ovulatory cycle among adolescent females in Ghana is low and this may be contributing to unwanted pregnancies. Public health interventions on the ovulatory cycle should target adolescent females who have lower levels of education and those who do not use contraceptives.